Pengaruh Lingkungan Bisnis dan Karakteristik Kewirausahaan Terhadap Kinerja Usaha Mikro Kecil di Pasar Kodam Brawijaya Surabaya - Anastasya Pramono; Diana Juni Mulyati; Ute Chairuz M. Nasution (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This study aims to investigate whether business environment (X1) and entrepreneurial characteristics (X2) influence the performance (Y) of micro-small enterprises (MSEs) in Pasar Kodam Brawijaya Surabaya. A newly established MSE may find it challenging to navigate in a competitive environment, necessitating anticipation of various possibilities to maintain business performance. The research adopts a quantitative approach with a sample of 287 respondents among business operators in Pasar Kodam Brawijaya Surabaya, selected through simple random sampling. Data analysis employs Multiple Linear Regression, t-test, F-test, and Coefficient of Determination. The findings indicate that both Business Environment and Entrepreneurial Characteristics have a significant simultaneous influence on Business Performance. Specifically, Entrepreneurial Characteristics exert a greater influence on business performance compared to the Business Environment. Therefore, entrepreneurs should focus on aspects such as customer growth, diversifying product offerings, and motivating employees to achieve business goals collaboratively. This approach enables businesses to navigate competitive challenges and sustain themselves under any conditions.